Socio-ecological Factors Influencing Farmers’ Perceptions on Water Management under Conservation Agriculture - Anwesha Mandal,; S. K. Acharya,; Monirul Haque, (Indian Journal of Extension Education, 2022)
Conservation agriculture (CA) is about conserving natural resources through optimum usage along with adopting proper management measures to cut down on excessive use of inputs. Minimum tillage and retention of crop residues on the field help in the conservation of soil moisture and will result in the saving of irrigation water. To inculcate the beneficial effects of CA for conserving water into the minds of the farmer, it is necessary to understand the existing perception of the farmers on water management and also the social as well as ecological factors that influence the perception build up in the farmers. The study was conducted in two districts i.e. Nadia and Hooghly of West Bengal under the new alluvial zone during the year 2018-19, depending on the agricultural intensity and propensity to arsenic contamination in the groundwater. Seventy-five respondents were identified through the snowball sampling method. The results show that variables like age of the farmer, fragmentation of land, income of the farmer per unit of land and stubble height maintained by the farmers have a strong correlation with the perception development of the farmers on water management.